Strain Improvement of Phosphate Solubilizing Fungal Strains - Ilyas*, Rajeshkumar Jayaraman and M.H.Muhammad (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">A laboratory study was conducted to isolate, investigate and enhance the phosphate solubilization efficiency of certain isolated fungal strains viz., Aspergillus niger, Aspergillus fumigatus, Penicillium sp. These fungal strains were isolated from the rhizosphere of paddy fields in Tamilnadu, India and screened for phosphate solubilization. The <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-bidi-font-weight: bold; mso-fareast-font-family: Calibri; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">enhancement of phosphate solubilization<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;"> of these strains was studied through three types of mutagenesis: UV, sodium azide and ethyl methane sulphonate mutagenesis. The mutant ANuv60 exhibited 127% increased efficiency for phosphate solubilization compared to the wild strains. Similarly, the phosphate solubilization by sodium azide mutant (ANsa120) was 133% higher and EMS mutant (ANems120) was 135% higher than the wild strain. The efficient strains were further studied for the effect of carbon and nitrogen source on phosphate solubilization. Significance of the findings is discussed in detail.